LEARNING EVALUATION OF THE LINK AND MATCH PROGRAM WITH THE WORLD OF BUSINESS/INDUSTRY ON LIGHT VEHICLE ENGINEERING SKILLS COMPETENCIES AT KARSA MULYA VOCATIONAL SCHOOL PALANGKA RAYA - Aldo Dese; Sri Muwantini (Jurusan Pendidikan Teknologi Dan Kejuruan, 2024)
This research aims to evaluate the Link and Match learning program in the Light Vehicle Engineering Competence, with ofocus on its integration with the business/industry. The evaluation covers aspects of context, input, process, and product, conducted at the school and the business/industry partner (DUD/), namely PT. Murni Ber/ion Motor Palangko Rayo (Mitsubishi Motors). The respondents include 30 students, 3 teachers/school administrators, and 3 representatives from the business/industry partner. Research data wos collected through surveys, interviews, and documentation, followed by descriptive analysis. The research findings indicate, firstly, that the implementation of the Link and Match program in the business/industry sector for the competence of light vehicle engineering is considered good based on teacher readiness, teacher competence, student preparedness, facilities, ond the collaboration between the vocational school and the business/industry. The evaluation of input by both students and teachers falls into the good category, with an overage score of 18.00. Secondly, the execution of the Link and Match program in the business/industry sector for the competence of light vehicle engineering is considered good based on the facilities and infrastructure of the industry class, the role of teachers, the role of students, and on-site work practices at the business/industry, with an average score of 17.07 by students ond 19.00 by teachers. To support the smooth implementation ond enhance the quality of the Link and Match program, it is recommended to provide more varied preparation for students' understanding of the material and to conduct in-depth evaluations of students' comprehension of the competence in light